TECHNOLOGY-ENHANCED FORMATIVE ASSESSMENT: UNRAVELING INDONESIAN EFL LEARNERS’ VOICES - Taufiqulloh, Taufiqulloh; Nindya, Meyga Agustia; Rosdiana, Ihda (University of Kuningan, 2023)
The current research works have put great concern on the positive impacts of the implementation of formative assessment in EFL learning and teaching. Simultaneously, the swift technological development also takes effect on supporting the practices of formative assessment. This study aims to explore EFL learners’ voices on implementing technology-enhanced formative assessment in EFL classrooms. It is a case study intended to obtain detailed information from the participants for a particular case. Five EFL learners from different universities were involved in this study by using a telephone interview. The findings of this study reveal that EFL learners have positive views on the use of formative assessment in terms of getting a better understanding and promoting learning independence. Besides, most EFL learners also perceived that the integration of technology-enhanced positively affects them in working with formative assessments assigned by the lecturers. The last, the challenges of technology-enhanced formative assessment by EFL learners comprised the overload of work assignments, the difficulty of time management, the incapability of staring at laptops for a long time, the instability of LMS, and the unclear instructions as well as insufficient feedback by the lecturers. Several implications are provided in this study.Keywords: challenges; EFL learners; formativ